Clinical Picture at Attendance and Response to Flexible Family-Based Low-Carb Life Style Change in Children With Obesity - Cakmak, Hatice Mine; IlknurArslanoglu; Sungur, Mehmet Ali; Bolu, Semih (International Journal of Child Health and Nutrition, 2021)
Aim: The study aims 1) to determine the clinical status of obese children at the admittance to the pediatric endocrinology referral center 2) to investigate the efficiency and compliance of the low-carb diet in a pediatric population with or without exercise, metformin Material and Methods: All subjects with the complaint of obesity and BMI percentile >95 were recruited from January 2012-August 2014. We evaluated basal retrospectively, recommended low carbohydrate family-wide eating practice and exercise to all, and metformin to selected cases, and recorded Self-reported adherence at first, third, sixth, and twelfth months. Results: Thirty-six subjects used metformin with a higher ratio of weight loss (90.0%, p=0.010) without a difference in the number of lost kilograms. In 160 cases without metformin; diet only, exercise only, and both diet and exercise groups lost weight significantly according to neither diet nor exercise group (OR:12.08, 95% CI 3.93-41.66, p<0.001; OR:3.04, 95% CI 1.18-7.84, p=0.022 and OR:32.80, 95% CI 7.14-150.77, p<0.001 respectively). Exercise plus diet (95.3%, p=0,002) and only diet (88.9%, p=0,023) were even more efficient than exercise alone (65.5%). In the twelfth month, 13.8% were on follow-up. Conclusion: Obesity gives rise to metabolic complications in the very early stages. A low carbohydrate diet proved to be acceptable and useful. Long-term consistency remains a challenge.